Differential expression and upregulation of interleukin-1α, interleukin-1β and interleukin-6 by freshly isolated human small intestinal epithelial cells - Laura Madrigal-Estebas; Derek G. Doherty; Diarmuid P. O'Donoghue; Conleth Feighery; Cliona O'Farrelly (Mediators of Inflammation)
Background: Small intestinal epithelial cells (SIEC) may contribute to local immune regulation.